Ta‘līm al-Lughah al-‘Arabiyyah bi-Kitāb al-‘Arabiyyah li al-Nāshi’īn li-Taḥsīn Mahārat al-Qirā’ah ladā Ṭullāb Madrasah Taḥfīẓ al-Qur’ān al-I‘dādiyyah: Pembelajaran Bahasa Arab dengan Kitab Al-‘Arabiyyah Li An-Nasyiin untuk Meningkatkan Kemampuan Qira’ah Siswa SMP Tahfidzul Qur'an - Imam Wahyudi; Ahmad Zaki Maulidi (STAI Nurul Huda Kapongan Situbondo, 2024)
Arabic language learning using the Al-‘Arabiyyah Li An-Nasyiin textbook is one of the methods to enhance students' reading skills (maharah qira’ah). This study aims to describe the implementation of the Al-‘Arabiyyah Li An-Nasyiin textbook as a learning medium and measure its impact on the maharah qira’ah abilities of eighth-grade students at SMP Tahfidzul Qur'an, Jember. The research employed a qualitative approach with data collection techniques including observation, interviews, and documentation. The results indicate that this method is effective in improving students' reading abilities, with an approach consisting of opening activities, core learning sessions, and closing activities. Students became more enthusiastic and capable of comprehending Arabic texts effectively. The implementation of this method offers a new alternative for enjoyable and effective Arabic language learning